Paths selection‐based resequencing queue length in concurrent multipath transfer. (28th April 2014) - Wang, Fenghua; Xie, Dongliang; Wang, Jingyu; Zhang, Peng; Shi, Yan
Summary Traditionally, concurrent multipath transfer (CMT) is used to achieve aggregate bandwidth in next generation networks, which are expected to be heterogeneous, integrating access networks employing different technologies. Simultaneous data transfer over multiple destination addresses could increase throughput, but causes data reordering at the destination. A lot of studies assumed that the receiver buffer (RBUF) in CMT is unlimited, actually, it's not. However, limited RBUF indeed affects the whole performance and even causes RBUF blocking problem in the real situation. In this paper, we analyze the RBUF blocking problem brought by simultaneous data transfer with limited RBUF. Then, we propose a new analytical model of reliable delivery to predict the Stream Control Transmission Protocol throughput and the length expectation of the resequenceing queue in CMT. Based on the model mentioned earlier, the paths selection problem is formulated as a knapsack problem, which maximizes the overall throughput and limits the resequencing queue length expectation to the fixed RBUF size. Through the computer simulations, the proposed analytical model can predict the throughput of CMT accurately. It is proved that our proposed paths selection has achieved much better performance than the others in CMT.Copyright © 2014 John Wiley & Sons, Ltd.